2024
DOI: 10.1002/ptr.8176
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of resveratrol on epigenetic mechanisms in age‐related diseases: A comprehensive review

Sale Zhang,
Farzam Kiarasi

Abstract: Recently, various studies have shown that epigenetic changes are associated with aging and age‐related diseases. Both animal and human models have revealed that epigenetic processes are involved in aging mechanisms. These processes happen at multiple levels and include histone modification, DNA methylation, and changes in noncoding RNA expression. Consequently, changes in the organization of chromatin and DNA accessibility lead to the regulation of gene expression. With increasing awareness of the pivotal func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 125 publications
0
2
0
Order By: Relevance
“…Resveratrol (RSV), found in a wide range of plants, has garnered attention as an anti-aging compound. (9) It has been associated with a variety of health-promoting effects and has demonstrated the potential to mitigate various diseases, including diabetes, neurodegeneration, and aging. (10)(11)(12) While the precise mechanisms underlying these functions are still debated, they may be attributed in part to their antioxidant properties and its ability to modulate mitochondrial functions.…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol (RSV), found in a wide range of plants, has garnered attention as an anti-aging compound. (9) It has been associated with a variety of health-promoting effects and has demonstrated the potential to mitigate various diseases, including diabetes, neurodegeneration, and aging. (10)(11)(12) While the precise mechanisms underlying these functions are still debated, they may be attributed in part to their antioxidant properties and its ability to modulate mitochondrial functions.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Chitcholtan and colleagues evaluated the anticancer effects of resveratrol, a natural compound with several beneficial effects [22][23][24][25], on ovarian cancer cell lines, i.e., OVCAR-8 and SKOV-3, grown on the chorioallantoic membrane (CAM) of chicken embryos. The authors found that resveratrol significantly reduced angiogenic activities, pNF-κB levels, and SLUG protein levels, suggesting that this compound may have the potential to impact the behavior of ovarian cancer progression.…”
mentioning
confidence: 99%